Thrombosis risk and in vitro fertilization - E. Grandone (IRBIS LLC, 2022)
Assisted reproductive technologies (ART) have been progressively recognized as a widely applied means to fight against infertility. Women after ART were shown to have higher risk of developing venous thromboembolism (VTE) that might be related to using some drugs, particularly gonadotropins. VTE risk emerges at relatively early time points after ovulation induction being sustained virtually until pregnancy is complete. According to the multi-center RIETE Registry (Spanish, Registro Informatizado de la Enfermedad TromboEmbolica), a risk of developing isolated pulmonary embolism (PE) is elevated in women after ART compared to those receiving hormonal contraceptives as well as women having spontaneous pregnancy. Low-molecular-weight heparins (LMWH) are justified to be used as a preventive means. However, commonly recommended preventive LMWH dose in such patient cohort may not always be sufficient. On the other hand, escalating dose for some LMWH results in increased rate of developing hemorrhages. Hence, it is important to take into consideration what exact type of LMWH as well as its dose and duration of therapy should be prescribed to women after ART that requires to be further investigated.